Aquaculture and Freshwater Fisheries Evolution and Prospects in Colombia - Heimo Mikkola (Contemporary Research and Perspectives in Biological Science Vol. 6, 2024)
Due to its geographical position, Colombia served as a crucial dispersal route for the first settlers who arrived in South America via Central America. These first peoples based their diet on fishing, hunting and collecting some plant products. Since the 1970s, Colombia has been aware of the importance of aquaculture and inland fisheries in the future of its economy due to the constant increase in the population that is increasingly in need of animal protein. In 1972, a joint project between the Government of Colombia and the Food and Agriculture Organization of the United Nations was approved to study inland fishing and aquaculture development in the country. The project describes the fish culture and fisheries research activities starting with the situation in the 1970s and comparing it with recent findings. A list of the main capture and culture fish species is given. Colombian fishing production has had great variations, but first inland water fishing was more important than marine. For instance, in 1972, total fish catch was 104,390 tons and 79% of that originated from inland waters. After the continental fisheries went down, the marine fisheries accounted in 2019 already 78 per cent of the total catch of the country. Mean standing fish crop estimates in 1975-76 from the bay, open water and vegetation habitats in four floodplain lakes were 118, 12 and 251 kg/ha indicating clearly that the fish productivity on the Magdalena floodplain was relatively low. The aquaculture sector has been growing rapidly, reflecting global trends, and producing more than capture fisheries. Aquaculture produced 88,000 tons in 2013, a three-fold increase from the mid-1990s. In 2020, total aquaculture production was already 179,351 tonnes and in the next year, the production was 192,521 tonnes with the annual growth rate being 7.3 per cent. The sector is largely dominated by inland freshwater pisciculture and small-scale farmers produce about a third of the total volume. Five species account for the bulk of production: Silver tilapia (a cross between the Blue tilapia Oreochromis aureus and Nile tilapia O. niloticus) and Red tilapia (a hybrid between the Blue and Mozambique tilapia O. mossambicus) contribute around two-thirds of the total volume, while Rainbow trout (Oncorhynchus mykiss), Pirapitinga (Piaractus brachypomus) and Tambaqui (Colossoma macropomum) each account for around 13%. Today aquaculture production supplies more than 90% of the freshwater and saltwater organisms consumed in the country. The fresh review concluded that Colombia has all the potential to develop tropical aquaculture, which should focus on native fish breeding, genetic improvement, high-tech aquaculture systems, and agro-industrial and fish biomass development valorisation. Future development prospects of inland fisheries and aquaculture are discussed and a mention is made of ornamental fish cultivation and trade. Colombia is one of the leading countries to prevent and control diseases in ornamental fish. No sport fishing activities were witnessed during the FAO project 1972-1979 in the Magdalena floodplain but nowadays sport fishing is practised in almost the entire national territory (80%). Sport fishing is a hobby for those to whom money or fish food is not the main object but more important is to get a good photo together with a big fish. Sport fishers practise all the catch and release systems so fish is not away from nature. This activity is an important income source in tourism and benefits the local fishers often in remote rural areas. Free-time fishing may not be so significant for the national economy but it has high value in social and recreational terms for many people from all walks of life. Some time ago fisheries researchers and fishing people started an eFish-network in South America to collect fish species and production data. Citizen science is a unique opportunity to generate information on fish and fishing at the scale of a large country like Colombia.